Back Cover: Tetrazine Carbon Nanotubes for Pretargeted In Vivo "Click‐to‐Release" Bioorthogonal Tumour Imaging (Angew. Chem. Int. Ed. 37/2020). Issue 37 (4th August 2020) - Li, He; Conde, João; Guerreiro, Ana; Bernardes, Gonçalo J. L.
Abstract : The caged fluorogenic near‐infrared probe tHCA is presented in the cover picture as a chained molecule. As demonstrated by G. J. L. Bernardes and co‐workers in their Research Article on page 16023, the activity of the probe can be restored by specific reaction with a tetrazine "key" in combination with single‐walled carbon nanotubes to recover the emission of the tHCA upon ligation and liberation.